Transport, climate change and the city - Hickman, Robin; Banister, David (Abingdon, Oxon : Routledge, 2014)
"Transport is the key sector where carbon dioxide (CO2) emissions are difficult to reduce. The book's original content and presentation draws on contemporary culture to demonstrate the need for a wider and more transparent debate on future travel behaviours and lifestyles, acceptability and implementability, and the potential for using different means to sell a different but attractive future"--Provided by publisher